INTEGRATED FARM BY MAKING OF "POC-FISH" AS THE ALTERNATIVE FOR ECONOMICAL COASTAL COMMUNITIES INCREASE - S. Syahrir; Djunarlin Toyang (Agrotech Journal, 2017)
Coastal communities play an important role in marine and fisheries development, as well as forming a culture in coastal areas. The socio-economic life of coastal communities in Kolakaasi Sub-District of Kolaka District is far from prosperous as the data obtained from Badan Pusat Statistik  of Kolaka (2015), the number of poor population in Kolaka reached 27,210 with the percentage of 14.68%. Partners in this IbM activity are teenagers who drop out of school environments and groups of housewives living in coastal areas. The problem of partners in the activities of IbM is the number of teenagers dropping out of school in the partner environment due to the low level of welfare of coastal communities so that the average level of the highest education is junior high school where the young women have to help the family economy by working as laborers in traditional markets of Kolaka or only help parents at home while the men work at sea. Fishing is highly dependence to the nature, so that if the weather is bad then the fishermen cannot gain  income. IbM-Integrated Farm by making "POC-FISH" is the manufacture of liquid organic fertilizer that combines agricultural activities with fisheries. POC-FISH is mad of small fish, commonly called lure fish (teri) by Kolaka community. This type of fish is abundant in Kolaka and sold cheaply (R.p 5,000/Kg). The purpose of this IbM activity was the empowerment of coastal communities through the transfer of science and technology by utilizing local potentials so that the partners involved can begin to be productive and economically independent by conducting business on a household scale. The method of making POC - FISH will be carried out simply so that technology transfer can be easily understood by partners. The process of transfer of science and technology was carried out with the pattern of 1) the education of the partner group on the importance of technology adoption by utilizing the potential and local wisdom that will be able to produce a product with higher economic/selling value 2) POC-FISH making training 3) mentoring partner group in marketing 4) monitoring and evaluation. The outgoing plan of this IbM activity is the publication of the ISSN national journal published in 2017 and POC-FISH Products